Microphytobentos of rivers of the North-Western Black Sea region (Ukraine) - Gerasimiuk, V.P. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2025)
The results of original, long-term studies of microphytobenthos in 12 rivers of the North-Western Black Sea region (NBR) are summarized and presented. The aim of the work was to study the taxonomic composition of microscopic algae in the rivers of the study area. As a result of processing 581 samples at 53 stations in 12 rivers, 431 species of microscopic algae were identified, belonging to 170 genera, 75 families, 38 orders, 12 classes, 6 divisions, 4 kingdoms, and 2 domains (empires). The species composition of the algal flora was represented by heterokonts (285 species), cyanobacteria (60), green (48), euglena (21), charophytes (13), and dinoflagellates (4). In the Danube River ― 288, Southern Bug ― 210, Dniester — 166, Velikiy Kuyalnik — 139, Baraboy — 126, Kodima — 105, Kuchurhan — 97, Tyligul — 90, Kamyanka — 75, Synyukha ― 67, Mertvovid — 55 and Yahorlyk — 54 species of algae were recorded. lmost half of the species composition (49.2%) was part of the 10 leading families: Bacillariaceae, Naviculaceae, Fragilariaceae, Euglenaceae, Scenedesmaceae, Cymbellaceae, Surirellaceae, Pinnulariaceae, Oscillatoriaceae and Selenastraceae. Representatives of the 10 leading genera Nitzschia Hassall (29 species), Navicula Bory (23), Pinnularia Ehrenb. (13), Surirella Turpin (12), Euglena Ehrenb. (10), Desmodesmus (F.Chodat) An, Friedl et E.Hegew. (9), Oscillatoria Vaucher ex Gomont (8), Phormidium Kütz. ex Gomont (8), Cymbella C.Agardh (8) and Gomphonema C.Agardh Ehrenb. (8) occupied a dominant position in the microphytobenthos of the rivers. In the following rivers, a number of rare species were identified for the waters of the North-Western Black Sea Region and the territory of Ukraine. 205 species of microphytes were found in macrophyte fouling, 176 in silt, 47 in stones, 37 in sand, 16 in river foam, and 11 in pond fouling.